Training report : clinical studies coordination in oncology - Simas, Ana Luísa Oliveira de (2014)
This report describes a curricular training experience in Study Coordination, developed at Unidade de Investigação Clínica (Clinical Research Unit) of Instituto Português de Oncologia do Porto Francisco Gentil, E.P.E. (Portuguese Oncology Institute-Porto), in the ambit of the Master in Pharmaceutical Medicine at University of Aveiro. This report describes the State of the Art in Pharmaceutical R&D Process in Europe, especially in Oncology, emphasising its current trends and stressing specificities of special and vulnerable populations, in the scope of the traineeship. The study coordination activities were essentially performed in the Pathology Clinics of Lung, Urology, Gynaecology, Paediatrics, and the Intensive Care Service. The activities developed had the main goal of acquiring experience in oncology clinical trials, while reinforcing the knowledge from my academic background. These activities included screening and randomisation of patients, preparation and processing of study visits, data entry and query resolution, and documents management, among other activities transversal to the 15 clinical trials, accompanied in the traineeship. Globally, the traineeship allowed a good overview of the activities involved in the conduction of clinical trials in a hospital, and a worthy introduction to the marketplace. I strengthened the knowledge acquired from my academic background. I developed competences and skills at the professional and personal level, such as dealing with unforeseen situations, and developed strategies to overcome challenges. I sharpened my vision of careers in clinical research, and hope to continue addressing new challenges in this area.